2020
DOI: 10.1002/slct.202000681
|View full text |Cite
|
Sign up to set email alerts
|

A New Facial Homoleptic Tris‐cyclometalated Iridium(III) Complex with Oxygen‐bridged Triarylamine Units

Abstract: A new facial homoleptic tris-cyclometalated phosphorescent iridium(III) complex Ir(ppyNO) 3 featuring three oxygen-bridged triarylamine units has been synthesized via an efficient Suzuki-Miyaura cross-coupling reaction of oxygen-bridged triarylamine unit based boron reagent 1-b with corresponding tribrominated iridium(III) complex Ir-Br. It can not only show an effective green light emission, but also display a narrower full width at half maximum (FWHM = 57 nm) and better solubility than that of the classical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…In this article, we choose the classic green phosphorescent iridium(III) complex Ir(ppy) 2 acac [34–35] (ppy=2‐phenylpyridine) as a model complex (Scheme 1), and then prepare a new yellow phosphorescent iridium(III) complex Ir(ppybop) 2 acac by introducing two oxygen‐bridged triphenylamine units into the 4 site of benzene ring of two ppy ligands, respectively. It is notable that this unit is first introduced into the ppy ligand and then formed an iridium complex, which is different from the previous synthetic route [32–33] where the unit is functionalized directly onto the iridium complex. It is found that the complex Ir(ppybop) 2 acac can show a larger redshift emission (λ em =568 nm), a narrower FWHM (59 nm), a longer emission lifetime (τ=3127 ns) and a better solubility than that of the classical green complex Ir(ppy) 2 acac (λ em =520 nm, FWHM=70 nm, τ=1206 ns).…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…In this article, we choose the classic green phosphorescent iridium(III) complex Ir(ppy) 2 acac [34–35] (ppy=2‐phenylpyridine) as a model complex (Scheme 1), and then prepare a new yellow phosphorescent iridium(III) complex Ir(ppybop) 2 acac by introducing two oxygen‐bridged triphenylamine units into the 4 site of benzene ring of two ppy ligands, respectively. It is notable that this unit is first introduced into the ppy ligand and then formed an iridium complex, which is different from the previous synthetic route [32–33] where the unit is functionalized directly onto the iridium complex. It is found that the complex Ir(ppybop) 2 acac can show a larger redshift emission (λ em =568 nm), a narrower FWHM (59 nm), a longer emission lifetime (τ=3127 ns) and a better solubility than that of the classical green complex Ir(ppy) 2 acac (λ em =520 nm, FWHM=70 nm, τ=1206 ns).…”
Section: Introductionmentioning
confidence: 87%
“…However, up to now, this new type of organic unit have been limited research in pure organic luminescent materials, and even less on metal complexes. In the recent work of our group, [28–33] this unit has been introduced as ligand skeleton or functional group into various phosphorescent metal complexes to regulate photophysical properties due to its strong electron donor, good planarity and strong rigidity.…”
Section: Introductionmentioning
confidence: 99%
“…Luminescent materials play an important role in chemical sensing, biological imaging and organic light-emitting diodes (OLEDs), and phosphorescent metal iridium(III) complex with d 6 electronic structure are particularly attractive as luminescent materials among many transition metals complexes in the past few decades due to its excellent optical properties and variable chemical structures. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Among the many iridium complexes, tris-cyclometalated facial phosphorescent iridium(III) complexes [17][18][19][20][21][22][23][24][25] featuring three same cyclometalated ligands have been proved to have more stable chemical structure and better optical performance compared with other types of iridium complexes. For example, the classic green-emitting facial phosphorescent iridium(III) complex fac-Ir(ppy) 3 [26] composed of three 2-phenylpyridine (ppy) ligands and its derivatives are widely studied and applied.…”
Section: Introductionmentioning
confidence: 99%